Scrapbooking for dummies - Wines-Reed, Jeanne (Wiley, 2004)
Scrapbooking is sweeping the nation! This hot hobby is a fantastic way to preserve your memories and family history—and have a lot of fun doing it. Now, here’s an easy-to-follow guide that will have you creating great scrapbook projects in no time. It is perfect for you if you’re a new scrapbooker who wants to create your own personal scrapbook (or who would like to make a special scrapbook for a friend or loved one) or if you’re already an avid scrapbooker who’s looking for helpful tips and new ideas. This friendly guide takes the guesswork out of creating well-designed albums.